2021
DOI: 10.1155/2021/8395048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Inflammatory Mediator Profiles in Sepsis Patients Reveals That Extracellular Histones Are Strongly Elevated in Nonsurvivors

Abstract: The timely recognition of sepsis and the prediction of its clinical course are challenging due to the complex molecular mechanisms leading to organ failure and to the heterogeneity of sepsis patients. Treatment strategies relying on a “one-fits-all” approach have failed to reduce mortality, suggesting that therapeutic targets differ between patient subgroups and highlighting the need for accurate analysis of the molecular cascades to assess the highly variable host response. Here, we characterized a panel of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…HMGB1 interacts with heparin via two positively charged domains, box A and box B ( Martinotti et al, 2015 ), and via its heparin-binding domain ( Xu et al, 2011 ). HMGB1 plasma levels are elevated in conditions associated with abnormal coagulation, including sepsis ( Eichhorn et al, 2021 ) and COVID-19, where HMGB1 has been correlated with disease severity ( Chen et al, 2020 ). The biological functions of HMGB1 resemble those of activated platelets, including the induction of DNA externalization in neutrophils ( Maugeri et al, 2014 ; Hoste et al, 2019 ) and microvascular thrombosis ( Ito et al, 2007 ).…”
Section: Platelets As Mediators Of Immunothrombosismentioning
confidence: 99%
“…HMGB1 interacts with heparin via two positively charged domains, box A and box B ( Martinotti et al, 2015 ), and via its heparin-binding domain ( Xu et al, 2011 ). HMGB1 plasma levels are elevated in conditions associated with abnormal coagulation, including sepsis ( Eichhorn et al, 2021 ) and COVID-19, where HMGB1 has been correlated with disease severity ( Chen et al, 2020 ). The biological functions of HMGB1 resemble those of activated platelets, including the induction of DNA externalization in neutrophils ( Maugeri et al, 2014 ; Hoste et al, 2019 ) and microvascular thrombosis ( Ito et al, 2007 ).…”
Section: Platelets As Mediators Of Immunothrombosismentioning
confidence: 99%
“…Notably, procalcitonin (PCT) and C-reactive protein (CRP) have been extensively considered biomarkers for the diagnosis and prognosis of sepsis [ 5 ]. More recently, cell-free DNA (cfDNA) and histones have been introduced as two biomarkers for sepsis prognosis which both reflects cellular death activity [ 2 , 6 , 7 , 8 , 9 , 10 ]. Nucleosomes consist of 145 bp DNA wrapped around a core histone octamer, which contains two copies of histones H2A, H2B, H3, and H4.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from antimicrobial defense of neutrophils (6,7), extracellular DNA (ecDNA) released during NETs formation is recognized as a damage-associated molecular pattern that further activates immune response. According to recent studies, markers of NETs formation can be perceived as markers of inflammation in a variety of pathologies including sepsis, multiple trauma, obesity, systemic autoimmune diseases and thrombosis (8)(9)(10)(11)(12)(13)(14)(15). Recently, studies of Yu and colleagues identified proteins derived from neutrophils (16) and NETs-like structures (17) in urine sediment of UTI patients.…”
Section: Introductionmentioning
confidence: 99%